Analyzing the Antioxidant Qualities of a Flower Extract from Camellia Sinensis - Sushmita Singh; Saurabh Srivastava (American Journal of Biology and Natural Sciences, 2025)
This study aimed to evaluate the antioxidant properties of the Camellia sinensis (tea plant) flower extract. While tea leaves are widely recognized for their medicinal properties, the antioxidant potential of the flowers has been relatively under-researched. In this investigation, flower extracts were prepared using various solvents (e.g., ethanol and water), and their free radical scavenging activities were tested. The results demonstrated that the Camellia sinensis flower extract possesses significant antioxidant activity, primarily attributable to the presence of polyphenolic compounds such as flavonols, catechins, and saponins. Notably, the ethyl acetate fraction of the ethanol extract exhibited the highest scavenging capacity against hydroxyl radicals (SC50 11.6 µg/mL). The total antioxidant capacity of the extracts was quantified using various in vitro assays, including DPPH, ABTS, and FRAP tests. <span lang="EN-US" style="font-size: 12.0pt; font-family: ’Palatino Linotype’,serif; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-font-kerning: 0pt; mso-ligatures: none; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The conclusion is that the Camellia sinensis flower is a rich and valuable natural source of antioxidants, possessing the potential to prevent or manage various health conditions related to oxidative stress. These findings open new avenues for the potential application of tea flower extract in functional foods, pharmaceuticals, and cosmetic products.